HUBUNGAN ANTARA PEMANFAATAN TWITTER DENGAN PEMENUHAN KEBUTUHAN INFORMASI MAHASISWA UKI DI ERA PANDEMI COVID-19 - Lidwina, Pricelia Ruth; Siahaan, Chontina; Moningka, Yesa Yulina (Jurnal Insani, 2022)
This study discusses the relationship between the use of Twitter and meeting the information needs ofstudents in the era of the Covid-19 pandemic. In this case, the researchers made Indonesian ChristianUniversity students class of 2020 as research objects. The problem in this study is whether there is arelationship between the use of Twitter and the information needs of UKI 2020 students. The purpose ofthis research is to determine whether there is a relationship between the use of Twitter and meeting theinformation needs of UKI 2020 students. The theory of information needs is the foundational theory usedin this research. because this theory really reflects where every human being has demands to meet theirinformation needs through various existing media according to their needs. This study uses a quantitativeapproach. Research data collection techniques through the distribution of questionnaires and alsoliterature study. Researchers used a proportional stratified random sampling technique. While the dataanalysis technique used is the correlation coefficient and also the significance. The results of this studyindicate that there is a significant relationship between the use of Twitter and the fulfillment of informationneeds. This statement is based on research results in hypothesis testing, which states that the value of rcount> rtable (0.0746 > 0.195) then Ho is rejected.